دراسة أثر نوع السماد العضوي في إنتاجية نبات البازلاء صنف روندو - سمرة بديع; سعيد هيام (مجلة جامعة تشرين للبحوث والدراسات العلمية- سلسلة العلوم البيولوجية, 2019)
أجريت الدراسة خلال الفترة 2009-2010 في مزرعة فديو التابعة لكلية الزراعة بجامعة تشرين, بهدف دراسة تأثير ثلاثة أنواع من الأسمدة العضوية وتحديد أفضلها تأثيراً في إنتاج نباتات البازلاء pisum sativum صنف روندو. اشتملت الدراسة على أربع معاملات هي: تسميد وثلاث معاملات تسميد عضوي (مخلفات أبقار ومخلفات أغنام وزرق دواجن ) بمعدل 2كغ/م2 و بثلاث مكررات للمعاملة الواحدة. تبين نتيجة الدراسة أن التسميد العضوي بمخلفات الأغنام قد أعطى أفضل النتائج مقارنة مع الشاهد, حيث أدى إلى زيادة في درجة امتلاء القرون بنسبة 35%مقارنة مع الشاهد, وأن أعلى إنتاجية للنبات من القرون الخضراء كانت في معاملة سماد الأغنام التي حققت زيادة معنوية مقدارها 136.4 غ / النبات ,تلتها معاملة زرق الدواجن بزيادة م مقدارها معنوية 115.9 غ / النبات مقارنة مع الشاهد.أما بالنسبة لإنتاج النبات الواحد من البذور الطازجة فقد حققت معاملة سماد الأغنام زيادة معنوية قدرها 44.88 غ/نبات ,بينما ساهم زرق الدواجن بزيادة معنوية مقدارها 21غ/نبات مقارنة مع الشاهد, وأن إنتاجية النبات من البذور الجافة ازدادت معنويا بنسبة513% في معاملة سماد الأغنام , و42% لزرق الدواجن زيادة على الشاهد. بينما أعطت معاملة سماد الأبقار أقل النتائج في المؤشرات المذكورة إلا أنه أعطى أعلى قيمة لدرجة تصافي القرون28.38. The experiment was carried out during 2009-2010 in Fidio farm belonging to The Faculty of Agriculture in Tishreen University, and aims to study the effect of the type of three organic fertilizers and to determine their effect on the productivity of green peas pissumsativa. The study included three indications: untreated control sample, and three fertilizer treatments (cow dung, sheep discharge, and chicken excrement)2kg/m2 with three replications per treatment. Results have shown that the organic fertilizer using sheep discharge yielded the best results compared with the control sample as it resulted in a 35% increase in pod fullness when compared with the control sample. The highest plant production of green pods was in the sheep fertilizer treatment as it yielded a 136.4g/plant increase in productivity followed by chicken excrement treatment with a 115.9g/plant increase compared with the control sample. In terms of a single plant’s production of fresh seeds, sheep fertilizer treatment yielded a 44.88g/plant increase whereas chicken excrement treatment contributed a 21g/plant increase compared with the control sample. Productivity of dry seeds per plant increased by 135% after using sheep fertilizer and 42% after using chicken fertilizer when compared with the control sample. Cow fertilizer treatment yielded the least results in the above-mentioned indexes but it yielded the highest value of seeds compared to yielded pods.